VERBALIZATION OF THE CONCEPT OF "GENEROSITY" IN THE ENGLISH LANGUAGE PICTURE OF THE WORLD (Intent Research Scientific Journal, 2023)
Starting from the generally accepted views, according to which each language has its own peculiarities of reflecting the picture of the world, linguists also distinguish a number of features and characteristics for the English language. In this case, it is legitimate to talk about the English language picture of the world; this has its own cultural dominants that differ from other languages.